Outdoor localization with optical navigation sensor, IMU and GPS - Yun, Y.; Jin, J.; Kim, N.; Yoon, J.; Kim, C. (IEEE International Conference on Multisensor Fusion and Integration for Intelligent Systems, 2012)
Autonomous outdoor navigation algorithms are required in various military and industry fields. A stable and robust outdoor localization algorithm is critical to successful outdoor navigation. However, unpredictable external effects and interruption of the GPS signal cause difficulties in outdoor localization. To address this issue, first we devised a new optical navigation sensor that measures a mobile robot's transverse distance without being subjected to external influence. Next, using the optical navigation sensor, a novel localization algorithm is established with Inertial-Measurement-Unit (IMU) and GPS. The algorithm is verified in an urban environment where the GPS signal is frequently interrupted and rough ground surfaces provide serious disturbances. ？ 2012 IEEE.